THE CURRENT STATE OF TOURISM INDUSTRY IN FRANCE - L. Efanova; V. Polyakova (Вестник университета, 2019)
Today France is one of the most visited countries in the world. The features of the tourism industry in France have been considered in the article. The purpose of the article is to study the current state of tourism in France and make forecasts for the near future. The phenomenon of excessive tourism has been highlighted, the reaction of the local population to sutourism has been reviewed and substantiated. The opinion of experts of the World Tourism Organization on excessive tourism has been adduced. The latest significant events, that can affect tourist flows, have been considered.